Adriano y Egipto - Reggiani, Anna Maria (ROMULA, 2012)
During work conducted in 2002 in the so-called "Grande Vestibolo" of Hadrian's Villa, facing the Cento Camerelle, a vast semicircular exedra was discovered connected to a fence and to two rectangular structures. This is a complex architectural arrangement in which coexist hydraulic elements, the art of gardening, and marble decorations. Among the finds of exceptional importance are those in Egyptianizing style, such as a fragment of a seated statue of the pharaoh Ramses II (1290 - 1224 b.C.) and various fragments of sculpture of humans and animals. The two rectangular structures are believed to have been two temples situated one in front of the other, decorated with precious marble, also in Egyptianizing style. This was a cult place tied to the Egyptian world, probably dedicated to the Bythinian love of the emperor Hadrian - Antinoos - who drowned in the Nile in the year 130 and was subsequently divinized. The latter may be testified by the finds of statues of Antinoos-Osiris. The complex is interpreted therefore as a Antinoeion datable to the years around AD. 135. ----------------------------------------------------------------- Sous Hadrien les cultes égyptiens atteignirent leur apogée. L'Empereur effectue deux voyages en Egypte (117 et 129/130). Son favori Antinous se noie dans le Nil lors du seconde voyage. Hadrien est très affecté par sa mort, au point que les contemporains se demandent s'il pourra continuer à assumer sa charge impériale. Antinous est divinisé, comme c'est souvent le cas pour les noyés dans le Nil, dont on croit qu'ils deviennent les serviteurs d'Osiris et les Egyptiens les représentent avec les attributs d'Osiris. Rapidement, les statues et les oeuvres d'art représentant le jeune homme se multiplient, et une ville est même fondée, Antinoopolis, sur le Nil. Les Grecs acceptent également Antinous comme un avatar d'Hermès. Cette nouvelle religion est reçue plus froidement, mais le culte du jeune homme se perpétuera dans la statuaire et sur les monnaies du IIème siècle. Dans villa Hadriana, Hadrien fit construire un Antinoeion; sa décoration comportera de nombreuses représentations d'Osirantinoos, forme égyptienne d'Antinous. Il fait aussi installer des oeuvres authentiques provenant d'Egypte et il fait réaliser des oeuvres contemporaines égyptianisantes.